Anti‐Metastatic Nanoparticles: Enhanced Melanoma‐Targeted Therapy by "Fru‐Blocked" Phenyboronic Acid‐Modified Multiphase Antimetastatic Micellar Nanoparticles (Adv. Sci. 11/2018). Issue 11 (21st November 2018) - Long, Yang; Lu, Zhengze; Mei, Ling; Li, Man; Ren, Kebai; Wang, Xuhui; Tang, Jiajing; Zhang, Zhirong; He, Qin
Abstract : The refractoriness of cancers results from the multi‐phase metastatic cascade that exists in most metastatic tumors. In article number1800229, Qin He and co‐workers establish a multifunctional self‐delivering 3‐aminophenylboronic acid ‐ low‐molecular‐weight heparin‐d ‐α‐tocopheryl succinate (PBA‐LMWH‐TOS) nanoparticle, which acts as both a nanocarrier and anti‐metastatic agent that acts on most hematogenous metastasis of cancers. Both of the hydrophilic segments and the hydrophobic segments could restrain tumor metastasis by acting on different phases of the metastatic cascade.